2005
DOI: 10.1037/0893-3200.19.2.314
|View full text |Cite
|
Sign up to set email alerts
|

The Interpersonal Process Model of Intimacy in Marriage: A Daily-Diary and Multilevel Modeling Approach.

Abstract: This study used daily reports of interactions in marriage to examine predictions from the conceptualization of intimacy as the outcome of an interpersonal process. Both partners of 96 married couples completed daily diaries assessing self-disclosure, partner disclosure, perceived partner responsiveness, and intimacy on each of 42 consecutive days. Multivariate multilevel modeling revealed that self-disclosure and partner disclosure both significantly and uniquely contributed to the contemporaneous prediction o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

20
372
4
4

Year Published

2011
2011
2023
2023

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 428 publications
(407 citation statements)
references
References 26 publications
20
372
4
4
Order By: Relevance
“…Self‐disclosure is integral to the formation and maintenance of positive interpersonal relationships (Altman & Taylor, 1973; Reis & Shaver, 1988). Receiving intimate disclosure increases interpersonal trust and liking of the discloser (Collins & Miller, 1994) and is likely to be reciprocated, leading to mutual interpersonal attraction (Laurenceau, Barrett, & Rovine, 2005). …”
Section: Introductionmentioning
confidence: 99%
“…Self‐disclosure is integral to the formation and maintenance of positive interpersonal relationships (Altman & Taylor, 1973; Reis & Shaver, 1988). Receiving intimate disclosure increases interpersonal trust and liking of the discloser (Collins & Miller, 1994) and is likely to be reciprocated, leading to mutual interpersonal attraction (Laurenceau, Barrett, & Rovine, 2005). …”
Section: Introductionmentioning
confidence: 99%
“…Additionally, past research has shown that people feel more positively about a relationship to the extent that it involves self-disclosure and perceived partner responsiveness (e.g., Aron, Melinat, Aron, Vallone, & Bator, 1997;Gore, Cross, & Morris, 2006;Laurenceau, Barrett, & Rovine, 2005).…”
Section: Development Of Relationship-specific Identificationmentioning
confidence: 99%
“…The need for intimacy and close connection with each other is one of the basic needs of each individual and is an important part of a marvelous marriage that, according to Sharer & Reis, is the result of an interpersonal experience (6,7,8), which its creation and preservation in marriage is a skill and art, which, in addition to mental health and healthy initial experiences, requires the acquisition of skills and performing special duties (9). Intimacy is the proximity, similarity and loving personal relationship with another that requires awareness, deep understanding, acceptance, and expression of thoughts and feelings.…”
Section: Introductionmentioning
confidence: 99%